A High-Resolution Map of Meiotic Recombination in Cryptococcus deneoformans Demonstrates Decreased Recombination in Unisexual Reproduction. Issue 2 (6th April 2018) - Roth, Cullen; Sun, Sheng; Billmyre, R Blake; Heitman, Joseph; Magwene, Paul M
Abstract: Multiple species within the basidiomycete genus Cryptococcus cause cryptococcal disease. These species are estimated to affect nearly a quarter of a million people leading to ∼180, 000 mortalities, annually. Sexual reproduction, which can occur between haploid yeasts of the same or opposite mating type, is a potentially important contributor to pathogenesis as recombination can generate novel genotypes and transgressive phenotypes. However, our quantitative understanding of recombination in this clinically important yeast is limited. Here, we describe genome-wide estimates of recombination rates in Cryptococcus deneoformans and compare recombination between progeny from α–α unisexual and a –α bisexual crosses. We find that offspring from bisexual crosses have modestly higher average rates of recombination than those derived from unisexual crosses. Recombination hot and cold spots across the C. deneoformans genome are also identified and are associated with increased GC content. Finally, we observed regions genome-wide with allele frequencies deviating from the expected parental ratio. These findings and observations advance our quantitative understanding of the genetic events that occur during sexual reproduction in C. deneoformans, and the impact that different forms of sexual reproduction are likely to have on genetic diversity in this important fungal pathogen.